Determinants of Occupational Health and Safety (OHS) Implementation: The Role of Knowledge Management, Work Discipline, and Organizational Culture in the Chemical Industry - Adenan Adenan; Muth Mainnah (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Occupational Health and Safety (OHS) remains a persistent challenge in industrial sectors, particularly in developing countries where workplace accidents continue to occur despite the implementation of safety regulations. Objective: This study aims to examine how knowledge management, work discipline, and organizational culture influence the effectiveness of OHS implementation in the chemical industry in Indonesia. Method: This research applied a quantitative explanatory approach involving 300 employees from a chemical manufacturing company (PT X). Data were collected through structured questionnaires and analyzed using multiple regression analysis, supported by tests of validity, reliability, and classical assumptions. Results and Discussion: The findings show that all independent variables significantly affect OHS implementation (p < 0.05). Organizational culture has the strongest influence (β = 0.410), followed by knowledge management (β = 0.308) and work discipline (β = 0.256). The model explains 65.5% of the variance in OHS implementation (R² = 0.655). Conclusion: These results indicate that OHS effectiveness is largely determined by the alignment between knowledge, employee behavior, and organizational values. Strengthening safety culture and encouraging behavioral-based safety practices are essential for improving sustainable safety performance in high-risk industries